The Brine Shrimp Artemia: Adapted to Critical Life Conditions - Gajardo, Gonzalo M.; Beardmore, John A. (Frontiers in Physiology, 2012)
The brine shrimp Artemia is a micro-crustacean, well adapted to the harsh conditions that severely hypersaline environments impose on survival and reproduction. Adaptation to these conditions has taken place at different functional levels or domains, from the individual (molecular-cellular-physiological) to the population level. Such conditions are experienced by very few equivalent macro-planktonic organisms; thus, Artemia can be considered a model animal extremophile offering a unique suite of adaptations that are the focus of this review. The most obvious is a highly efficient osmoregulation system to withstand up to 10 times the salt concentration of ordinary seawater. Under extremely critical environmental conditions, for example when seasonal lakes dry out, Artemia takes refuge by producing a highly resistant encysted gastrula embryo (cyst) capable of severe dehydration enabling an escape from population extinction. Cysts can be viewed as gene banks that store a genetic memory of historical population conditions. Their occurrence is due to the evolved ability of females to “perceive” forthcoming unstable environmental conditions expressed by their ability to switch reproductive mode, producing either cysts (oviparity) when environmental conditions become deleterious or free-swimming nauplii (ovoviviparity) that are able to maintain the population under suitable conditions. At the population level the trend is for conspecific populations to be fragmented into locally adapted populations, whereas species are restricted to salty lakes in particular regions (regional endemism). The Artemia model depicts adaptation as a complex response to critical life conditions, integrating and refining past and present experiences at all levels of organization. Although we consider an invertebrate restricted to a unique environment, the processes to be discussed are of general biological interest. Finally, we highlight the benefits of understanding the stress response of Artemi